Libsys+: A QR Code-Based Resource Management Implementing the Apriori Algorithm for an Innovative Library Solution - Callos, Francis C.; Mojares, Philip V. (International Journal of Computing Sciences Research; Vol 9 (2025): Volume 9, 2025)
Purpose – The purpose of this study was to address the growing need for libraries to adapt to technological advancements, enhance access to information, and innovate services through information technology and secure networks. Specifically, it aimed to develop a QR code-based system that optimizes resource management and facilitates seamless retrieval of library resources. Method – The study employed a mixed-methods research strategy, integrating qualitative and quantitative approaches. The development process was guided by the modified waterfall model, ensuring systematic progression through requirements analysis, design, implementation, testing, and deployment. A key feature of the system was the implementation of the Apriori algorithm, which analyzed user interactions and borrowing trends to provide personalized recommendations for resources. Testing included unit, system, and acceptance evaluations using ISO 25010 standards. The Apriori algorithm used for resource recommendations is tailored to current library usage trends. The implementation of the QR code and Apriori algorithm may be constrained by the available network infrastructure in certain library settings, particularly in institutions with limited technological resources or internet connectivity. Results – The results demonstrated a high level of functional suitability, with the system achieving a mean score of 4.15 (SD = 0.82). This indicates significant enhancements in resource management efficiency and user satisfaction. Conclusion – The study concludes that integrating QR code technology and Apriori algorithms into library management systems improves accessibility, streamlines operations, and enhances the overall user experience. Recommendations – The study recommends further refinement of the algorithm to accommodate diverse user needs and future integration with mobile applications for broader accessibility. Research Implications – The study suggests that other institutions can adapt similar approaches to modernize library systems. Practical Implications – This highlights the potential for operational cost savings and improved service delivery. Social Implications – The system fosters equitable access to library resources, promoting lifelong learning and inclusivity in educational environments. This study demonstrates that innovative technologies can revolutionize library services, serving as a benchmark for modernizing resource management in academic institutions.